Bone marrow fibre content in acute myeloid leukaemia before and after treatment. Issue 11 (November 1984) - Islam, A; Catovsky, D; Goldman, J M; Galton, D A
Abstract : Bone marrow fibre content was studied in 34 patients with acute myeloid leukaemia at presentation and subsequently after chemotherapy and at complete remission. The findings indicate that: some degree of marrow fibrosis is present in about one third of the patients with acute myeloid leukaemia at presentation; effective antileukaemia treatment may result in reversal of marrow fibrosis; and increase in marrow fibre content at diagnosis does not affect haemopoietic regeneration after treatment and achievement of complete remission.